Corporate governance as an instrument of change state owned companies: the case of the Hellenic telecommunications organization - Spanos, Loukas J.; Papoulias, Demetrios B. (2005)
"This paper analyses the evolution of Corporate Governance (CG) mechanisms and organizational changes of the Hellenic Telecommunication Organization (HTO) and has two objectives: to enrich the debate and to contribute to the increasing body of literature by examining and analyzing the organizational and institutional changes taken place in the HTO; and to place the HTO's case within the international debate regarding the privatization of state-owned companies and the importance of CG mechanisms as instruments of change. It is argued that the privatization of state-owned companies, when is accompanied with appropriate reform measures, can produce multiple positive effects. CG reforms were the main instruments that used in order to prepare the telecommunications incumbent to face the open and competitive markets."